Producción de vino espumoso a partir de residuos de zanahoria (2021)
The objective of this project is to obtain a sparkling wine-type alcoholic beverage from residual carrot, considering the large amount of material that is obtained in each production cycle for not meeting quality standards; which offers a good alternative to avoid economic losses in the producers of this vegetable in the country. Initially, a bibliographic review of the physicochemical properties of carrots was carried out in order to identify whether it is suitable for carrying out an alcoholic fermentation. Once recognized and analyzed, the experimental design of the variables was developed, the concentration of juice in the must of 100 and 50% in order to obtain a wine that meets the standards established by NTC1588. After a physicochemical and microbiological characterization carried out on batch 2, it turned out to meet the parameters allowed in the physicochemical properties, but it was not considered suitable for human consumption by not ensuring the permissible index of quality justified in the lack of asepsis.